ASSOCIATION BETWEEN WORKING EXPERIENCE AND DYSLIPIDEMIA AMONG INDONESIAN SEAFARER - Ardhea Jaludamascena; Dwi Retnoningrum (Universitas Muhammadiyah Semarang, 2017)
Seafarers were exposed to many occupational hazards, such as accidents, infectious diseases, workrelated stress, environmental stress and chronic diseases. Longer working experience means more exposed to these occupational hazards. Morbidity and mortality rate from chronic diseases tend to increase among seafarers. Dyslipidemia is one of independent risk factor of cardiovascular disease among seafarer. The aim of this study is to determine association between working experience and dyslipidemia among Indonesian seafarer. A cross sectional study was conducted on 157 Indonesia male seafarers who came to certified health care for their annual health examination from the beginning of January 2017 until the June 2017. The health examination data encompassed seafarer‟s age, height,weight, body mass index and lipid profile were collected. Seafarers were divided into two groups based on their work experience in sea each groups, then, categorized into with and without dyslipidemia subgroup. Dyslipidemia was defined as having two or more serum lipid profile abnormalities. The prevalence of dyslipidemia was 29.9%. Statistic analysis shown that longer working experience (more than 10 years) had more risk to have dyslipidemia about 3.5 times (95% CI = 1.66-7.59). There was association between working experience and dyslipidemia. Keyword : seafarer, dyslipidemia, lipid profile, occupational health